Heavy work investment for the accounting profession in Romania at time of Coronavirus pandemic - Florin Mihai; Mirela Stan; Gabriel Radu; Valentin Florentin Dumitru (Amfiteatru Economic Journal, 2020)
Heavy work investment in various domains of activity has not been sufficiently explored. This paper investigates how accounting professionals in Romania perceived different aspects related to the heavy work investment during the coronavirus pandemic. Professional accountants devote, by the nature of their job, many hours of work. In March 2020, unprecedented measures were taken in Romania in the context of the coronavirus pandemic. These include the obligation to work remotely where possible. The study' objective is to establish the socio-economic implications generated by the COVID-19 pandemic vis-à-vis accounting professionals and the activities of the financial-accounting department within the organizations during the affected period. The data were collected between April and June 2020 by distributing a questionnaire online and were processed using the SPSS software. The research results show that professional accountants have adapted quite quickly to distance work. Work during the pandemic generated additional stress and fatigue, but had positive influence on the work-family relationship and productivity. The research results show that the respondents' perception of work was influenced by the following variables: the age of the respondents, the city where they work, the way of carrying out the profession (employee or freelancer), and the size of the company where they work. The results obtained can be used by managers and regulatory bodies.
Keywords: M49; M54; 330; Heavy Work Investment; accounting profession; Romania; pandemic; remote work